Comparative dielectric parameters and conductivity mechanisms of pyridine-based rod-like liquid crystals - Yilmaz Canli, Nimet; Ocak, Hale; Okutan, Mustafa; Karanlik, Gurkan; Bilgin Eran, Belkiz (TAYLOR & FRANCIS LTD, 2020)
In this study, the dielectric properties and ac conductivity mechanism of pyridine-based rod-like liquid crystals (LC1andLC2), which show enantiotropic smectic A mesophase, have been investigated by impedance spectroscopy within the frequency interval of 1 kHz-2 MHz. The variation of real and imaginary component of dielectric constant with angular frequency has been investigated. The temperature-dependent absorption coefficient alpha, relaxation time tau(o), dielectric strength value Delta epsilon, temperature-dependent changes on crystal, SmA and Iso phases have been given. These values were obtained by fitting the experimental results in epsilon '-omega graph with the Cole-Cole equation real equation and Origin Pro Graph program. The frequency dependence of ac conductivities has also been analyzed. Different conductivity mechanisms, i.e. dc conductivity, correlated barrier hoping and quantum mechanical tunneling behaviors have been determined for different frequency regions.
Keywords: Liquid crystal; impedance spectroscopy (IS); dielectric properties (DP); conductivity mechanism; SERIES; TRANSPORT; Crystallography; Physics